2015
DOI: 10.1021/pr500983v
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Protein Expression Across Laboratory and Field Experiments in Geobacter bemidjiensis

Abstract: Bacterial extracellular metal respiration, as carried out by members of the genus Geobacter, is of interest for applications including microbial fuel cells and bioremediation. Geobacter bemidjiensis is the major species whose growth is stimulated during groundwater amendment with acetate. We have carried out label-free proteomics studies of G. bemidjiensis grown with acetate as the electron donor and either fumarate, ferric citrate, or one of two hydrous ferric oxide mineral types as electron acceptor. The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…A greater number of proteins were observed while D. reducens was either reducing sulfate (with lactate as electron donor) or fermenting pyruvate compared with Fe(III)-reducing conditions. The soluble and insoluble Fe(III)-reducing proteomes, analyzed for the first time in a Gram-positive organism, were distinctive from one another, a result consistent with findings in the Gram-negative metal-reducing organisms Geobacter sulfurreducens and Geobacter bemidjiensis (Ding et al, 2008 ; Merkley et al, 2015 ). Peptides for the sole MHC annotated in the genome (Dred_0700-1) were detected only on the insoluble Fe(III) condition, and an enzyme involved in heme biosynthesis was upregulated >100-fold on Fe(III)-oxide relative to pyruvate.…”
Section: Discussionsupporting
confidence: 78%
“…A greater number of proteins were observed while D. reducens was either reducing sulfate (with lactate as electron donor) or fermenting pyruvate compared with Fe(III)-reducing conditions. The soluble and insoluble Fe(III)-reducing proteomes, analyzed for the first time in a Gram-positive organism, were distinctive from one another, a result consistent with findings in the Gram-negative metal-reducing organisms Geobacter sulfurreducens and Geobacter bemidjiensis (Ding et al, 2008 ; Merkley et al, 2015 ). Peptides for the sole MHC annotated in the genome (Dred_0700-1) were detected only on the insoluble Fe(III) condition, and an enzyme involved in heme biosynthesis was upregulated >100-fold on Fe(III)-oxide relative to pyruvate.…”
Section: Discussionsupporting
confidence: 78%
“…There is no known physiological function for the homologs of these cytochromes in cultured organisms, and so the significance of these clades cannot be determined. Proteomic and transcriptomic experiments in Anaeromyxobacter dehalogenans 2CP-C ( 47 ), Geobacter sulfurreducens ( 48 ), Geobacter bemidjiensis ( 49 ), and Desulfuromonas acetoxidans ( 50 ) showed that these cytochromes are not expressed during metal respiration. However, metal respiration donates electrons to the extracellular environment rather than accepting them from external sources.…”
Section: Resultsmentioning
confidence: 99%
“…Homologs of cyc2 are also found in Geobacter spp. , specifically G. bemidjiensis, G. uraniireducens , and Geobacter M18, M21, and Rf64, members of a clade that predominates in aquifers (Holmes et al , 2007; Merkley et al , 2015). These organisms reduce Fe(III), though it is thought that this happens via the Omc system.…”
Section: Cyc2 Homologs In Other Fe-cycling and Extracellular Electronmentioning
confidence: 99%
“…These organisms reduce Fe(III), though it is thought that this happens via the Omc system. A study on the G. bemidjiensis proteome showed that the Cyc2 homolog Gbem_3353 was expressed at same levels during Fe(III) and fumarate reduction (Merkley et al , 2015), so function remained unclear, but could involve a more general EET role.…”
Section: Cyc2 Homologs In Other Fe-cycling and Extracellular Electronmentioning
confidence: 99%